Determinants Of Online Purchase Intention For Halal Cosmetic Products: Green Brand Perception, Halal Certification, And Digital Word-Of-Mouth - Rauf, Abdul; Hamdani, Hamdani; Raihan, Muhamad Syahrul (Universitas Muhammadiyah Tangerang, 2025)
This study investigates the underexplored intersection of sustainable branding, halal certification, and digital consumer engagement in shaping purchase decisions for halal cosmetic products. Focusing on Kahf Facial Wash sold via Shopee Indonesia, the research addresses a critical gap in understanding how these factors collectively influence e-commerce transactions in the rapidly growing Muslim beauty market. Employing a quantitative approach, data was collected through an online survey of cosmetic consumers and analyzed using descriptive and inferential statistical techniques. The findings reveal that green brand perception exerts a significant positive influence on purchase decisions, underscoring the rising consumer preference for environmentally conscious beauty brands. Interestingly, while halal labeling and online reviews did not demonstrate significant individual effects, their synergistic combination with green branding collectively enhanced consumer purchasing behavior. This suggests that modern Muslim consumers prioritize eco-friendly attributes as a primary driver, with halal certification serving as a baseline expectation rather than a differentiator. The study contributes novel insights to halal marketing theory by challenging conventional assumptions about religiosity as the dominant purchase driver. Practically, it offers actionable strategies for cosmetic brands to leverage sustainability narratives while maintaining halal compliance in digital marketplaces. For e-commerce platforms, the results highlight the need to optimize green branding displays alongside user-generated content to boost conversion